'Off everyone's radar': Australian women's experiences of medically necessary elective caesarean section - Bayes, S.; Fenwick, J.; Hauck, Yvonne (Elsevier, 2012)
Introduction: Despite an exponential rise in the number of medically initiated elective caesarean sections over the last two decades, women's experiences of this birth mode remain largely unknown. The aim of this study was to address this gap by describing women's experiences of medically necessary elective caesarean section. Methods: A grounded theory approach was used to collect and analyse interview data collected from 28 Australian women who had an elective caesarean section for a medical reason, 14 of whom were also observed during their caesarean section. The analyses of the non-participant observations were used to contextualise the women's experiences. Findings: Prior to having their baby, women expected to play an active part in their caesarean section and to be supported to take up their ‘mother’ role as soon as their baby was delivered. Postnatally however, they reported having felt invisible, superfluous and disregarded during the event. There was evidence that hospital routines and processes contributed to women feeling displaced and unimportant in their baby's birth. Three sub-categories were formed from the analysis of the data that together are represented by the in-vivo label ‘off everyone's radar’. These were ‘just another case on an operating list’, ‘striving to be included while trying to behave’ and ‘unable to be my baby's mum’.Discussion: Our findings suggest that when women are ignored during childbirth, any fear they hold may escalate into peritraumatic disassociation, which in turn has implications for women's postnatal mental and emotional health in the short and long term. In addition, the separation of the mother–baby dyad was found to have a devastating impact on maternal–newborn attachment that lasted well into the postnatal period. To optimise women's childbirth satisfaction and foster their attachment to their baby, both of which are essential for ongoing emotional well-being, it is vital that they are located at the centre of their birth experience and that if at all possible they are not separated from their newborn.